NKX2-8/PTHrP Axis-Mediated Osteoclastogenesis and Bone Metastasis in Breast Cancer - Abudourousuli, Ainiwaerjiang; Chen, Suwen; Hu, Yameng; Qian, Wanying; Liao, Xinyi; Xu, Yingru; Song, Libing; Zhang, Shuxia; Li, Jun (Frontiers in Oncology, 2022)
Bone metastasis is one of the most common distant metastasis of breast cancer, which could cause serious skeletal disease and increased cancer-related death. Therefore, identification of novel target(s) to develop therapeutics would improve patient outcomes. The role of NKX2-8 in modulation of bone remodeling was determined using osteoclastogenesis and micro-CT assays. The expression of NKX2-8 was examined via immunohistochemistry analysis in 344 breast cancer tissues. The mechanism underlying NKX2-8-mediated PTHrP downregulation was investigated using biotinylated deactivated Cas9 capture analysis, chromatin immunoprecipitation, co-immunoprecipitation assays. A bone-metastatic mouse model was used to examine the effect of NKX2-8 dysregulation on breast cancer bone metastasis and the impact of three PTHrP inhibitor on prevention of breast cancer bone metastasis. The downregulated expression of NKX2-8 was significantly correlated with breast cancer bone metastasis. In vivo bone-metastatic mouse model indicated that silencing NKX2-8 promoted, but overexpressing NKX2-8 inhibited, breast cancer osteolytic bone metastasis and osteoclastogenesis. Mechanistically, NKX2-8 directly interacted with HDAC1 on the PTHrP promoter, which resulted in a reduction of histone H3K27 acetylation, consequently transcriptionally downregulated PTHrP expression in breast cancer cells. Furthermore, targeting PTHrP effectively inhibited NKX2-8-downregulation-mediated breast cancer bone metastasis. Taken together, our results uncover a novel mechanism underlying NKX2-8 downregulation-mediated breast cancer bone metastasis and represent that the targeting PTHrP might be a tailored treatment for NKX2-8 silencing-induced breast cancer bone metastasis.